Karakteristik Buah Melon (Cucumis Melo L.) Pada Perlakuan Komposit Edible Coating Pati Singkong - Kitosan - Kesuma, Regina Tara; Hartiati, Amna; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2026)
Melon (Cucumis melo L.) is a climacteric fruit with an average water content of 95,19%, vitamin C content of 6,91%, and sweetness level of 4,43°Brix, making it commonly consumed in its fresh form with a relatively short shelf life. This study aimed to determine the effect of the ratio of cassava starch–chitosan edible coating composite on the quality characteristics of minimally processed melon and to determine the ratio of cassava starch – chitosan edible coating composite that produces the best characteristics in handling minimally processed melon during storage period. The experimental used a Completely Randomized Design (CRD), consisting of five treatment combinations of cassava starch to chitosan ratios: P1 (91,67:8,33), P2 (83,33:16,67), P3 (75:25), P4 (66,67:33,33), and P5 (58,33:41,67). Each treatment was replicated three times, with storage continuing until visible spoilage occurred. The parameters observed included weight loss, firmness, total soluble solids, and vitamin C content. The results demonstrated that the cassava starch–chitosan edible coating composite had a significant effect on weight loss, total soluble solids, and vitamin C content, but did not significantly affect the firmness of the minimally processed melon during storage. Among the treatments, the P5 formulation (58,33:41,67) produce the best characteristic of processed melon fruit that lasts for at least 8 days storage period, as evidenced by a weight loss of 7,38%, firmness of 15,80 N, total soluble solids content of 6,06°Brix, and vitamin C content of 4,35%.